Photocarboxylation of Benzylic C–H Bonds - Meng, Qing-Yuan (J Am Chem Soc, 2019)
[Image: see text] The carboxylation of sp(3)-hybridized C–H bonds with CO(2) is a challenging transformation. Herein, we report a visible-light-mediated carboxylation of benzylic C–H bonds with CO(2) into 2-arylpropionic acids under metal-free conditions. Photo-oxidized triisopropylsilanethiol was used as the hydrogen atom transfer catalyst to afford a benzylic radical that accepts an electron from the reduced form of 2,3,4,6-tetra(9H-carbazol-9-yl)-5-(1-phenylethyl)benzonitrile generated in situ. The resulting benzylic carbanion reacts with CO(2) to generate the corresponding carboxylic acid after protonation. The reaction proceeded without the addition of any sacrificial electron donor, electron acceptor or stoichiometric additives. Moderate to good yields of the desired products were obtained in a broad substrate scope. Several drugs were successfully synthesized using the novel strategy.